TM4SF4 is a diagnostic biomarker accelerating progression of papillary thyroid cancer via AKT pathway - Lizhi Lin; Jialiang Wen; Tiansheng Xu; Yuhao Si (Cancer Biology & Therapy, 2024)
The incidence of papillary thyroid cancer (PTC) has been steadily rising, though the underlying mechanism remains unclear. This study aims to elucidate the biological role of TM4SF4 in the PTC progression. Our differential expression analysis indicated that TM4SF4 was significantly upregulated in PTC, which was corroborated in both our local cohort and the data from Human Protein Atlas. Additionally, clinical characteristics analysis and receiver operating characteristic curves (ROC) demonstrated that TM4SF4 served as a significant diagnostic marker for PTC. Correlation and enrichment analysis of TM4SF4-related partners suggested that it was involved in cell junction and cohesion processes. Furthermore, immune infiltration analysis revealed a positive correlation between TM4SF4 expression and the immune activation in PTC. Importantly, in vitro experiments demonstrated that TM4SF4 downregulation suppressed the proliferation and metastasis of PTC cell lines while inducing apoptosis. We further discovered that the AKT activator SC79 was able to reverse the malignant behaviors suppression caused by TM4SF4 knockdown, suggesting that TM4SF4 may promote PTC progression via the AKT pathway. In conclusion, our study highlights the oncogenic role of TM4SF4 in PTC and identifies it as a novel biomarker for diagnosis and treatment.